Influence of flow disturbances on the performance of industry-standard LNG flow meters. (March 2021) - Kenbar, Asaad; Schakel, Menne
Abstract: In the last decade significant progress has been achieved in the development of measurement traceability for LNG inline metering technologies such as Coriolis and ultrasonic flow meters. In 2019, the world's first LNG research and calibration facility has been realised thus enabling calibration and performance testing of small and mid-scale LNG flow meters under realistic cryogenic conditions at a maximum flow rate of 200 m 3 /h and provisional mass flow measurement uncertainty of 0.30% ( k  = 2) using liquid nitrogen as the calibration fluid. This facility enabled, for the first time, an extensive test programme of LNG flow meters under cryogenic conditions to be carried out to achieve three main objectives; the first is to reduce the onsite flow measurement uncertainty for small and mid-scale LNG applications to meet a target measurement uncertainty of 0.50% ( k  = 2), the second is to systematically assess the impact of upstream flow disturbances and meter insulation on meter performance and the third is to assess transferability of meter calibrations with water at ambient conditions to cryogenic conditions. SI-traceable flow calibration results from testing six LNG flow meters (four Coriolis and two ultrasonic, see acknowledgment section) with water in a water calibration facility and liquid nitrogen (LIN) in the LNG research and calibration facility under various test conditions are fully described in this paper. Water and LIN calibration data were compared and it was observed that the influence of removing the meter insulation on mass flow rate measurement accuracy can be more significant (meter error > ±0.50%) than the influence of many typical upstream disturbances when the meter is preceded by a straight piping length equal to twenty pipe diameters (20D) with no additional flow conditioning devices, in particular for ultrasonic meters. The results indicate that the correction models used to transfer the water calibration to cryogenic conditions (using LIN) can potentially result in mass flow rate measurement errors below ±0.5%, however, the correction models are specific to the meter type and manufacturer. This work shows that the target measurement uncertainty of 0.50% can be achieved if the expanded standard error of the mean value measured by the meter is smaller than 0.40% ( k  = 2). It is planned to repeat these tests with LNG in order to compare the results with the LIN tests presented in this paper. This may reveal that testing with an explosion safe and environmentally friendly fluid such as LIN produces representative results for testing LNG flow meters. Highlights: First cryogenic flow calibration data from the LNG research & calibration facility. Cryogenic meter calibration errors within ±0.50% for about 85% of the calibrations. Effect of meter insulation on meter error can be larger than .|±0.50%| Water flowrate measurement accuracy of 0.10–0.15% is generally met. Water-to-cryogenic calibration transferability within 0.50% uncertainty is feasible.